Dominasi Budaya pada Implementasi New Normal dalam Menghadapi Pandemi Covid-19 - Pratisto Tinarso (Al-Ulum, 2021)
This study focuses on the cultural domination effect in society in the New Normal era.  This study is a field study. The data was collected through data inventory, then is analyzed and interpreted.  The result of this research showed three aspects of new normal culture in society, firstly, ideally, the New normal lifestyle should be socialized in society cultural forum, such as forum group discussion, colloquy, seminar, etc.  Secondly, the society will be more familiar with the New Era lifestyle, when its implementation accommodates cultural values of society and respect the ritual ceremony of custom and culture. Thirdly, the New Normal lifestyle implementation will be more convenient to be accepted in society, when it improved the role of custom and society leaders. Fourthly, the definition and the meaning of the New Normal lifestyle, nowadays, should be enriched by the meaning of health care in line with a cultural society that tends to community health care more than to personality health care.